Towards the Industry 4.0 agenda: Practitioners' reasons why a digital transition of shop floor management visualization boards is warranted - Pernille Clausen (Digital Business, 2023)
Under the umbrella of Industry 4.0 (I4.0), manufacturing companies have implemented various digital solutions, improving productivity. Shop floor management (SFM) is the core management instrument in manufacturing and is a precondition for implementing new systems. In recent decades, visualization boards (VB) have played a significant role in facilitating SFM. Following the I4.0 agenda, tremendous investments in manufacturing technologies have been spent to enable data-driven decision-making to support SFM in monitoring and controlling manufacturing. However, it does not seem that the digital transition has reached the SFM practice yet. Currently, most manufacturers rely on analog VBs. One would think, that applying such an analog tool limits the opportunities to harvest the full potential of the digital investments to improve SFM conditions. This paper aims to shed light on this gap by contributing to the existing literature on digital SFM by adding to the discussion on how the role of analog VBs as an SFM instrument is changing due to the digital transition of manufacturing. The research follows a case study approach, including 16 cases that illustrate the use of current VBs to facilitate SFM in 16 international companies. The findings demonstrate an SFM model (The Danish SFM model) which indicates that VBs are indispensable tools to facilitate SFM. Given the functionalities of current digital VBs provide limitations, analog VBs still prove useful to the SFM practice. Despite practitioners are experiencing challenges within their digital transition of SFM VBs, the findings highlight eight reasons why a digital transition is warranted.
Keywords: 650; Digital transition; Industry 4.0; Manufacturing; Shop floor management; Visualization boards